1981
DOI: 10.1001/archinte.141.5.635
|View full text |Cite
|
Sign up to set email alerts
|

The irritable bowel syndrome. A clinical review and ethical considerations

Abstract: The irritable bowel syndrome (IBS) is clinically characterized by a wide variety of symptoms, including dyspepsia, flatulence, nausea, cramping abdominal pain, constipation and/or diarrhea, and nonspecific symptoms, probably reflecting autonomic nervous system overreactivity. Physiologically, the colonic motor abnormality is characterized by an altered slow-wave rhythm, quantitative differences from normal in the repetitive contraction pattern of the rectosigmoid area, and increased colonic muscle responsivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The theory that the gut is hypersensitive is old, 3 but it has become the dominant hypothesis 53 . It can embrace other theories that irritable bowel syndrome is due to diet, 54 primary motility disturbance, 55 , 56 psychosocial distress 57 or infection 58 ,.…”
Section: Education and Reassurancementioning
confidence: 99%
See 1 more Smart Citation
“…The theory that the gut is hypersensitive is old, 3 but it has become the dominant hypothesis 53 . It can embrace other theories that irritable bowel syndrome is due to diet, 54 primary motility disturbance, 55 , 56 psychosocial distress 57 or infection 58 ,.…”
Section: Education and Reassurancementioning
confidence: 99%
“…Ignorance breeds contempt. In the past, some inexperienced hospital doctors have labelled patients complaining of irritable bowel syndrome symptoms as ‘crocks’ and ‘neurotics’ 3 . We have since learned much about the prevalence, prognosis and clinical presentation of irritable bowel syndrome and these data provide clues that help us to manage the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…More than 70 years ago, Bockus and others (1928) suggested that functional gastrointestinal symptoms were related to an imbalance or dysfunction within the ANS. Twenty years ago, Kirsner (1981) theorized that IBS symptoms were due to several patterns of ANS alteration, including "ANS overreactivity." A series of laboratory investigations led by various researchers has indicated that, at least for a subset of patients with functional bowel disorders (e.g., functional dyspepsia, IBS), ANS dysfunction may be present (Hausken and others 1993;Lindgren and others 1991;Camilleri and Fealey 1990;McAllister and others 1990).…”
mentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is characterized clinically by abdominal pain and altered bowel habits (Maxwell et al, 1997) and may include symptoms such as dyspepsia, flatulence, nausea, cramping, constipation and/or diarrhoea (Kirsner, 1981). Although there is considerable symptom overlap with organic abdominal disease and other functional gastrointestinal disorders (Talley, 1998), reliable diagnostic criteria for IBS are available (Manning et al, 1978;Thompson et al, 1992).…”
Section: Introductionmentioning
confidence: 99%